Role of endothelial nitric oxide synthases system on acute appendicitis - TAŞLIDERE, BAHADIR; TASLIDERE, BAHADIR; TAŞLIDERE, ELİF; ŞENER, Elif Funda; Taslidere, ELİF; GUNAY, Nahide Ekici; BOL, Oguzhan; BULBUL, Emre; Aktas, Ramazan Sami; GÜNAY, Nurullah (My University, 2016)
BACKGROUND: Obstruction and inflammation of the appendix lumen is the leading physiopathological process during acute appendicitis (AA). Although the relationship between inflammation and endothelial nitric oxide synthases (eNOS) has been well described, no recent data describing the relationship between inflammation during AA and polymorphism of the eNOS gene has been reported. Given the limited data available, we believed that defining the relationship between AA and eNOS would be a beneficial contribution. METHODS: A total of 201 patients admitted to the emergency department with AA and 201 healthy volunteers selected from among the relatives of patients were included. Polymorphism of the eNOS was assessed. RESULTS: Intron 4a/4a was positive in 119 participants, genotype G894T GT was positive in 71 patients with AA, and 786-1 was positive in 71 patients with AA. These results suggest that no statistically significant correlation exists between genotypes of AA patients and control subjects regarding 4a/b, G894-GT, and 786-1 eNOS polymorphisms. CONCLUSION: Though the present results suggest that no statistically significant correlation exists between AA and eNOS gene polymorphism, to claim otherwise is also impractical. We believe that the present results will lay the groundwork for future, larger studies.